2016
DOI: 10.7554/elife.18882
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and neonatal hematopoietic progenitors are functionally and transcriptionally resistant to Flt3-ITD mutations

Abstract: The FLT3 Internal Tandem Duplication (FLT3ITD) mutation is common in adult acute myeloid leukemia (AML) but rare in early childhood AML. It is not clear why this difference occurs. Here we show that Flt3ITD and cooperating Flt3ITD/Runx1 mutations cause hematopoietic stem cell depletion and myeloid progenitor expansion during adult but not fetal stages of murine development. In adult progenitors, FLT3ITD simultaneously induces self-renewal and myeloid commitment programs via STAT5-dependent and STAT5-independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…Lin28b is highly expressed in fetal HSCs and HPCs, but levels decline in neonatal progenitors, both in mice and humans. [32][33][34] To our surprise, sustained Lin28b expression suppressed rather than accelerated AML formation, suggesting that it may afford protection from MLL rearrangements during fetal stages before its expression declines in neonates. This may explain why, in humans, MLL rearrangements often occur prior to birth but overt leukemias do not usually arise until after birth.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Lin28b is highly expressed in fetal HSCs and HPCs, but levels decline in neonatal progenitors, both in mice and humans. [32][33][34] To our surprise, sustained Lin28b expression suppressed rather than accelerated AML formation, suggesting that it may afford protection from MLL rearrangements during fetal stages before its expression declines in neonates. This may explain why, in humans, MLL rearrangements often occur prior to birth but overt leukemias do not usually arise until after birth.…”
Section: Introductionmentioning
confidence: 79%
“…Transplantations were performed as described previously. 32 All animals were housed in a pathogen-free barrier facility, and all procedures were performed according to an Institutional Animal Care and Use Committee-approved protocol.…”
Section: Mouse Strains and Husbandrymentioning
confidence: 99%
See 1 more Smart Citation
“…Murine fetal progenitors have greater engraftment efficiency, biased lineage differentiation, and altered susceptibility to transformation compared with adult counterparts (24)(25)(26)(27). Analogous studies in humans showed that fetal and cord blood CD34 + cells are more proliferative and have a greater propensity to form myeloid colonies in methylcellulose culture than do adult cells (28,29).…”
Section: Introductionmentioning
confidence: 79%
“…Altogether, this work suggested that Flk2 expression was associated with loss of self-renewal potential and initiation of robust proliferation in adult hematopoietic progenitors (10)(11)(12)14). During fetal hematopoiesis, however, activity of the FlkSwitch system correlated very differently with HSC phenotype and transplantability as compared to adult hematopoiesis, giving rise to the identification of the fetal drHSCs recently reported by Beaudin and coworkers (10 (16,17). Although transplantation assays have been instrumental to rigorously and prospectively define HSCs, findings by Beaudin and coworkers highlight the fact that transplantation into irradiated recipients remains an experimental assay, and that behavior of a given population of progenitors after transplantation (e.g., long-term reconstitution from drHSCs) does not necessarily match their in vivo activity (e.g., spontaneous disappearance of these cells in physiological conditions).…”
mentioning
confidence: 89%